Association of GST gene polymorphism and noise-induced hearing loss Running title: GST gene polymorphism and NIHL - Ziba Loukzadeh; Hadi Eshaghi Sani; Mohammad Hasan Sheikhha; Farzaneh Morteza Ratki (AIMS Press, 2019)
Background: It has been proposed that Noise-induced hearing loss is a complex disease that is combination of environmental and genetic factors. There are inconsistent results concerning the association between variation in glutathione S-transferase (GST) genetic polymorphisms (GSTT1 rs1049055 and GSTM1 rs10712361) and susceptibility to Noise-induced hearing loss. Objective: This study was designed to assess the association between GST gene polymorphism and Noise-induced hearing loss among noise-exposed workers. Methods: In a case-control study, male workers from tile and ceramic factories were selected randomly. Subjects were classified into two groups according to the result of audiometry: 73 subjects showed Noise-induced hearing loss which was considered in the case group and 87 subjects without hearing loss was enrolled in the control group. The GSTT1 and GSTM1 polymorphism of both groups were assessed by multiplex polymerase chain reaction. Results: Null GSTT1 and GSTM1 genotypes were more frequent in case group but no significant statistical difference was seen in case and control groups. No significant link between GSTT1 and GSTM1 genotypes was found. Conclusion: This study suggests that the genetic variability of GSTT1 and GSTM1 has no effect on susceptibility to noise induced hearing loss.